Accessibility, people with disabilities, museums, and online exhibitions: trends in a bibliographic review (Perspectivas em Ciência da Informação, 2024)
To understand the relationship between accessibility, people with disabilities, museums, and online exhibitions, we conducted a bibliographic review systematized in the PublicAcessibilidade and Periódicos Capes databases. After applying the exclusion criteria, we analyzed 18 texts through full reading and associating them with the textual processing of their abstracts in the qualitative analysis software IRAMUTEQ. Five classes emerged: 1, Visitors with disabilities: online experience and information; 2, Digital technologies and accessibility provision; 3, Websites: accessibility techniques and tools; 4, Educational perspectives; 5, Development, implementation, and interpretation of online exhibitions. The results indicate practices and trends in the promotion of accessibility in online museums through reports of development and evaluation of websites and exhibitions, in a mostly technical perspective, in addition to theoretical and empirical discussions about the influence of accessibility resources on the inclusion of PWDs. In the selected texts, we also identified that there are gaps when it comes to the approach of the experience of visiting PWDs to online exhibitions. Finally, we emphasize that, although extremely important, investigations in this universe should not focus only on technicalities, but that it is still necessary to study, reflect, and discuss the social and historical implications of this relationship, especially to ensure that PWDs are protagonists and active participants in both practice and theory.